(untitled) (Research, Society and Development, 2020)
Objective: To describe the prototyping process of artificial blood bags based on Design Thinking for health education actions on transfusion therapy. Method: Descriptive study, type of experience report, on prototyping of artificial blood bags for health education action related to transfusion therapy, from the processes of immersion, ideation and prototyping of Design Thinking, in a public hospital in the city of Rio de Janeiro. Results: The immersion phase allowed a broader view of the central problem and connections to solution-oriented processes. The Brainstorming technique supported the ideation process of the artificial blood bag prototyping with collective, empathic and creative discussions and constructions. Prototyping started during the choice of the ingredients needed to make the artificial blood. Tests and adjustments were made to adjust the color, viscosity and permeability. The testing of the prototype was carried out in health education actions on transfusion therapy, with the participation of 93 nursing professionals. Conclusion: The Immersion, ideation and prototyping steps of Design Thinking allowed the development of an artificial blood bag prototype, which after testing proved to be valid, technologically feasible, economically viable and with the possibility of reproduction in other educational activities.